2018
DOI: 10.1111/liv.13933
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus infection and risk of non‐alcoholic fatty liver disease: A population‐based cohort study

Abstract: Metabolic factors play an important role in the presence of NAFLD among Chinese CHB patients. However, viral replication factors are not related to NAFLD except among those with concurrent type 2 DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 30 publications
4
43
0
Order By: Relevance
“…In addition, Viganò et al retrospectively analysed 235 treatment‐naïve patients with CHB and found that biopsy‐proven liver steatosis was not associated with virologic factors, such as HBeAg status or HBV‐DNA load. Moreover, Zhu et al followed 2393 Chinese patients with CHB who had no history of alcohol intake or NAFLD over a ‐year period, and found no association between viral factors and NAFLD incidence rate. Therefore, HBV itself might not be associated with NAFLD independently.…”
Section: Decreased Risk Of Nafld Onset In Patients With Hbv Infectionmentioning
confidence: 99%
“…In addition, Viganò et al retrospectively analysed 235 treatment‐naïve patients with CHB and found that biopsy‐proven liver steatosis was not associated with virologic factors, such as HBeAg status or HBV‐DNA load. Moreover, Zhu et al followed 2393 Chinese patients with CHB who had no history of alcohol intake or NAFLD over a ‐year period, and found no association between viral factors and NAFLD incidence rate. Therefore, HBV itself might not be associated with NAFLD independently.…”
Section: Decreased Risk Of Nafld Onset In Patients With Hbv Infectionmentioning
confidence: 99%
“…The prevalence of NAFLD in patients with CHB ranges from 18% to 40% . Concomitant metabolic factors play an important role in the development of NAFLD amongst CHB patients and increase the risk of liver disease progression independent of viral load or hepatitis activity . However, whether NAFLD interferes with LSM values in CHB patients is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with elevated ALT of more than 35 were 166 (72.2%) and 143 (62.2%) had moderate to severe liver steatosis as determined by the controlled attenuation parameter. A population-based Chinese cohort study underscored the importance of metabolic factors as a cause of NAFLD in hepatitis B and excluded any possible relationship between viral factors and NAFLD but observed that in a subgroup of subjects with concurrent type 2 diabetes mellitus, detectable HBV DNA levels were negatively associated with the development of NAFLD (HR, 0.37; 95% CI, 0.14‐0.98) [11]. Peng D, by using liver biopsy as a tool, concluded that apart from metabolic factors, the hepatitis B virus indirectly facilitates the development of steatosis, as there existed a correlation between ALT levels, HBV DNA, and steatosis [12].…”
Section: Discussionmentioning
confidence: 99%